FICAG: personal financial planning interactive card games / Nurhannan Ainal Hairol Faizi ... [et al.] - Hairol Faizi, Nurhannan Ainal; Idris, Nurul Syahirah; Shahromizam, Nurhannani Zulaikha; Baharim, Muhammad Haziq; Mohamed, Munirah (Universiti Teknologi MARA, Kedah, 2023)
Personal financial planning plays a crucial role in our lives, yet many individuals struggle to develop the necessary skills to manage their finances effectively. FICAG is an interactive and innovative approach to learning personal financial planning with card games. The problem with learning personal finance through traditional methods is that they can often be dull and fail to engage students. Without an understanding of personal financial planning, students are more likely to engage in impulsive spending, accumulate debt, or fail to save for future goals. This can lead to financial instability and difficulties in managing their finances effectively throughout their lives. The primary objective of learning personal financial planning through card games is to give early exposure to financial literacy among secondary school students. By engaging in card games that incorporate financial concepts, players can gain a deeper understanding of fundamental principles such as saving, spending, budgeting, and risk assessment. The games provide an interactive and practical learning experience that promotes financial knowledge. The novelty of this card game allows players to experience and practice personal finance concepts in a hands-on and experiential manner, and it is designed for secondary school students. FICAG offers numerous benefits to society by improving financial literacy, fostering practical financial skills, promoting long-term financial well-being, and reducing financial stress. Due to a growing recognition of the importance of financial literacy among secondary school students, these card games can be commercialized by introducing them to educational institutions. It can serve as a valuable educational tool in classrooms, offering an engaging and interactive way to learn financial concepts. Companies can also position themselves as leaders in the financial education space while providing valuable resources.